If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 3)(X + 3) = -1 Reorder the terms: (3 + 3x)(X + 3) = -1 Reorder the terms: (3 + 3x)(3 + X) = -1 Multiply (3 + 3x) * (3 + X) (3(3 + X) + 3x * (3 + X)) = -1 ((3 * 3 + X * 3) + 3x * (3 + X)) = -1 ((9 + 3X) + 3x * (3 + X)) = -1 (9 + 3X + (3 * 3x + X * 3x)) = -1 (9 + 3X + (9x + 3xX)) = -1 (9 + 3X + 9x + 3xX) = -1 Solving 9 + 3X + 9x + 3xX = -1 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + 3X + 9x + -9 + 3xX = -1 + -9 Reorder the terms: 9 + -9 + 3X + 9x + 3xX = -1 + -9 Combine like terms: 9 + -9 = 0 0 + 3X + 9x + 3xX = -1 + -9 3X + 9x + 3xX = -1 + -9 Combine like terms: -1 + -9 = -10 3X + 9x + 3xX = -10 Add '-9x' to each side of the equation. 3X + 9x + -9x + 3xX = -10 + -9x Combine like terms: 9x + -9x = 0 3X + 0 + 3xX = -10 + -9x 3X + 3xX = -10 + -9x Reorder the terms: 10 + 3X + 9x + 3xX = -10 + -9x + 10 + 9x Reorder the terms: 10 + 3X + 9x + 3xX = -10 + 10 + -9x + 9x Combine like terms: -10 + 10 = 0 10 + 3X + 9x + 3xX = 0 + -9x + 9x 10 + 3X + 9x + 3xX = -9x + 9x Combine like terms: -9x + 9x = 0 10 + 3X + 9x + 3xX = 0 The solution to this equation could not be determined.
| ln(8x^5)=ln(5x)+3 | | 9(5+v)=-90 | | -4=-9+w | | -100+(-77)= | | 2x+x+4x= | | F(x)=x^4-4x^3+16 | | -12x^2+19x-22=0 | | 63-2x=70 | | 30=x-.25x | | -3x-5x=2x+10 | | -25x+25=75 | | 8+5c+5= | | 0=40+15t-4.9t^2 | | 0.4=0.08 | | 2a*(-3a^2)= | | 3+9x=-6 | | 8x+1=7-1x | | 15-0.06x=5 | | 4+17x-3=9x+31-7x | | 3x-4=56-9x | | 9x+13=-8 | | 10x+3=4x+39 | | 3,570=34(p+30) | | 90=30x | | 6n^3-4n^2= | | 6m^2-23m-18=0 | | 5x^2+2c+8=0 | | 6x-yx=5 | | ln(5-3)=ln(5)-ln(3) | | c(x)=7x+569 | | 52=c-46 | | x(x+8)-(25x+3x)=0 |